Predictive factors for recurrent febrile seizures in children - Pengekuten Marudur; Elisabeth Herini; Cahya Dewi Satria (Indonesian Pediatric Society Publishing House, 2012)
Background One􀁡third of children who experience febrile seizures have a recurrence, '\.Vith rates of75% in the first year, and 90% mthin the second year following the first febrile seizure. Predictive factors for recurrent febrile seizures have been reported in studies from other countries, but there have been few of these studies in Indonesia. Objective To determine predictive factors for the recurrence of febrile seizures in children. Methods Children w i t h first􀁡time febrile seizures were prospectively followed up, for at least 12 months. Subjects were recruited consecutively from August 2008 to April 20 1 0 from two hospitals in Yogyakarta and one hospital in Klaten. We monitored recurrences of febrile seizure by telephone or home visits to parents every 3 months. Time to first recurrence of febrile seizures was analyzed using the Cox regression model. Results T here were 196 children v,ith first􀁡time febrile seizures who completed the follow up. Recurrent seizures were observed in 56 children (28.6%). Me811 follow up time was 21.7 (SD 6.6) months. Temperature of <40"C at the time of seizure (RR=2.29, 95%CI 135 to 3.89, P=0.OO2), history of febrile seizures in first􀁡degree relatives (RR=330, 95%CI 1.25 to 8.08, P<O.OOl), age at first febrile seizure of <12 months (RR􀁢2.40, 95%CI 1.42 to 4.06, P􀁢O.OOI) and duration of fever before the seizure of:51 hour (RR=4.62, 95%CI: 1.35 to 15.80, P=0.015) were significantly associated v,ith recurrence of febrile seizures. Furthermore, Cox regression analysis revealed that the age of < 12 months, history of febrile seizures in first􀁡degree relatives and temperature of < 40" C were significantpredictive factors for the recurrence of febrile seizures. Conclusion Age at first seizure of < 12 months, history of febrile seizures in first􀁡degree relatives, and seizure v,ith temperature of <40"C were independent predictive factors for recurrent febrile seizures in children. [Paediatr lndones. 2012;52:317,23].